Analisis Spasial Perkembangan Ekonomi Wilayah Kabupaten Sukoharjo Tahun 2008-2014 - irawati, Astri, Drs.H.M. Musiyam MTP, Dra.Hj.Umrotun, M.Si (2016)
Economic development is a process that causes the increment of population per capita income in a certain society for a long term period, coincide with the change of the important characteristics of thus certain society, which is the change in technological things, society mindset, as well as in institutional case. This research is aimed at determining economical sector in Sukaharjo Regency as a substance consideration in in the region economic development planning. The methodology applied in this research is secondary data methodology from the Regional Gross Domestic Product of Sukoharjo Regency and its sub districts in 2008-2014. The analysis instruments used are Location Quotient (LQ), analisis Shift Share, and Geographic Information System. The result analysis of Location Quotient shows the basis sector for Weru, Bulu, and Sukoharjo sub districts are three bases, for Tawangsari, Nguter, Bendosari, Polokarto, Mojolaban, and Grogol Sub Districts are four bases sector, for BakiGatak, and Kartasura Sub District are fife bases sector. The result of shift share analysis shows that the competitive sector grows faster than the regency which are Weru, Bulu, BendosariPolokarto, and Mojolaban sub district consist of six sectors, for Sukoharjo, Nguter, Gatak Sub districts are five sectors, for Tawangsari sub district is four sectors, Grogol, Baki, and Kartasura Sub District are three sectors. The conclusion from the Location Quotient and Shift Share analysis result is that it can be determined that superior sector potential with progress and rapidly grows sector classifications, basis sector, and competitive sector that grow faster from the regency. Those mentioned sector are industry sector which are located in Kartasura, Grogol, and Sukoharjo Sub District. The electrical, gas and clean water sectors are located in Sukoharjoo Sub District. The building sector is located in Grogol Sub District. Hotel and restaurant trade Sector is located in Bendosari, Nguter, Bulu, and Weru Sub District. Transportation and communication sectors are located in Gatak, Baki, Bendosari, and Bulu Sub District. Services sector is located in Gatak, Baki, Mojolaban, Polokarto, Tawangsari, Nguter, and Weru Sub District.